Cytotoxicity and inhibition of leukemic cell proliferation by sesquiterpenes from rhizomes of Mah-Lueang (Curcuma cf. viridiflora Roxb.) - Songyot Anuchapreeda (2018)
© 2017 Elsevier Ltd. Curcuma cf. viridiflora Roxb., also known as Mah-Lueang in Thai, belongs to the Zingiberaceae family and is grown from rhizomes. The rhizome of the plant has been used for medicinal purposes, in particular, to treat paralysis in Thai traditional medicine. However, no biologically active compounds have been reported from Mah-Lueang yet. In this study, natural compounds were isolated from Mah-Lueang and structurally determined by spectroscopic methods, including electrospray ionization mass spectrometry and nuclear magnetic resonance. The four isolated compounds were identified as furanodiene (1), dehydrocurdione (2), germacrone-4,5-epoxide (3), and zedoarondiol (4). These sesquiterpenes were investigated for antileukemic activities against KG1a and Molt4 cells. Leukemic cell proliferation is regulated by the Wilms' tumor 1 (WT1) transcription factor. Compound 1 showed the strongest cytotoxicity against both KG1a and Molt4 cells. Noncytotoxic concentrations (20% inhibitory concentration values) of all compounds were able to decrease the WT1 protein expression and total cell numbers in both cell lines. The four compounds showed good inhibitory activities for WT1 protein expression. Compounds 3 and 4 showed excellent antileukemic activities for both cell lines. In summary, four sesquiterpene compounds with antileukemic activities against the KG1a and Molt4 cell lines were identified in Mah-Lueang extracts.